2013
DOI: 10.4236/ojpchem.2013.34018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bifunctional Poly(Vinyl Phosphonic Acid-<i>co</i>-glycidyl Metacrylate-<i>co</i>-divinyl Benzene) Cation-Exchange Resin and Its Indium Adsorption

Abstract: Poly(vinyl phosphonic acid-co-glycidyl methacrylate-co-divinyl benzene) (PVGD) and PVGD containing an iminodiacetic acid group (IPVGD), which has indium ion selectivity, were synthesized by suspension polymerization, and their indium adsorption properties were investigated. The synthesized PVGD and IPVGD resins were characterized using Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) and mercury porosimetry. The cation-exchange capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the spectrum of Figure 2C, the peak at 1144 cm -1 was due to -P = O vibrations and the absorption bands at 1025 and 970 cm -1 were ascribed to the P-OH stretching bands. Previously, it was reported that cation-exchange resin containing the VPA group shows a strong peak at about 1194 and 965 cm -1 (22). The absence of the peaks corresponding to the vinylic and acrylic groups at around 1635-1610 cm -1 indicates that membranes were successfully prepared with high conversions of PEGDA and VPA.…”
Section: Structural Characterization Of Membranesmentioning
confidence: 98%
“…In the spectrum of Figure 2C, the peak at 1144 cm -1 was due to -P = O vibrations and the absorption bands at 1025 and 970 cm -1 were ascribed to the P-OH stretching bands. Previously, it was reported that cation-exchange resin containing the VPA group shows a strong peak at about 1194 and 965 cm -1 (22). The absence of the peaks corresponding to the vinylic and acrylic groups at around 1635-1610 cm -1 indicates that membranes were successfully prepared with high conversions of PEGDA and VPA.…”
Section: Structural Characterization Of Membranesmentioning
confidence: 98%
“…[1][2][3] However, there are several issues on ITO, which includes high supply cost as a rare earth element, harmfulness to the environments, and lack of flexibility (not suitable to the most recent technology of flexible displays). [4][5][6] For these reasons, a new transparent conductive material with physical flexibility and high adhesiveness to various functional materials of advanced electron and optical devices, such as oxide/metal/oxide multilayers, [7][8][9][10][11] metal grid, 12) silver (Ag) nanowire, 13) poly(ethylene dioxythiophene)poly(styrene sulfonate) (PEDOT:PSS), 14) carbon nanotube (CNT), 15) and graphene, is highly necessitated. Among these materials, recently, graphene has been attractive owing to its extremely high carrier mobility, low sheet resistance, and high transmittance.…”
Section: Introductionmentioning
confidence: 99%